Test reduction: I--Introduction and review of published work. Issue 6239 (23rd August 1980) - Card, W I; Emerson, P A
Abstract : The word "test" is used in a more general sense to describe the process of eliciting evidence of any kind from a patient, and this paper explores the thesis that much evidence is unnecessary and that therefore much test reduction is possible. The value of test reduction can be measured by its efficiency--that is, its effect on the misclassification of disease--or, preferably, by some measure of its cost-effectiveness.